Protein Kinase A in Human Retina: Differential Localization of Cβ, Cα, RIIα, and RIIβ in Photoreceptors Highlights Non-redundancy of Protein Kinase A Subunits - Roa, Jinae N.; Ma, Yuliang; Mikulski, Zbigniew; Xu, Qianlan; Ilouz, Ronit; Taylor, Susan S.; Skowronska-Krawczyk, Dorota (Frontiers in Molecular Neuroscience, 2021)
PKA signaling is essential for numerous processes but the subcellular localization of specific PKA regulatory (R) and catalytic (C) subunits has yet to be explored comprehensively. Additionally, the localization of the Cb subunit has never been spatially mapped in any tissue even though ~50% of PKA signaling in neuronal tissues is thought to be mediated by Cb. Here we used human retina with its highly specialized neurons as a window into PKA signaling in the brain and characterized localization of PKA Ca, Cb, RIIa, and RIIb subunits. We found that each subunit presented a distinct localization pattern. Ca and Cb were localized in all cell layers (photoreceptors, interneurons, retinal ganglion cells), while RIIa and RIIb were selectively enriched in photoreceptor cells where both showed distinct patterns of co-localization with Ca but not Cb. Only Ca was observed in photoreceptor outer segments and at the base of the connecting cilium. Cb in turn, was highly enriched in mitochondria and was especially prominent in the ellipsoid of cone cells. Further investigation of Cb using RNA BaseScope technology showed that two Cb splice variants (Cb4 and Cb4ab) likely code for the mitochondrial Cb proteins. Overall, our data indicates that PKA Ca, Cb, RIIa, and RIIb subunits are differentially localized and are likely functionally non-redundant in the human retina. Furthermore, Cb is potentially important for mitochondrial-associated neurodegenerative diseases previously linked to PKA dysfunction.